Exploring the rationales minor injury patients have for taking or not taking analgesia (pain relief) prior to attending the Emergency Department (ED) - Nutt, Charlotte (2012)
It is estimated that around 75% of patients attending an emergency department are experiencing varying degrees of pain on arrival. Despite this many minor injury patients have not taken any form of analgesia. The aim of this research study was to explore the rationales minor injury patients had for taking or not taking pain relief prior to attending the emergency department. The study adopted a broadly qualitative approach. A convenience sample of 56 patients who were streamed into the minor injury department completed a brief questionnaire. The questionnaire asked basic demographic questions and details regards pain level and whether participants had taken pain relief. 6 of these participants then took part in the in-depth interviews, which allowed exploration of rationales to take or not take pain relief. The findings revealed that pain was reported by 85% of the participants. 50% of the participants were stated they were in pain had taken analgesia and 50% had not. The findings suggest that there may be gender and age differences between those who took analgesia and those who did not. The qualitative data revealed 5 key themes these were: Knowledge and opinion of injury/ illness, past experiences, coping and suffering, advice and opinions of over the counter pain relief medication. The study shows that patients‘ rationales for taking or not taking analgesia are multifactorial. These rationales appear to be linked closely with health beliefs. Future research is recommended to further investigate how patients can be empowered to take analgesia before arrival. Until this can be achieved current practice needs to ensure that policy is being adhered to, ensuring that patients‘ pain is being assessed within 20 minutes of arrival. This would help to reduce the amount of pain experienced by our patients whilst waiting for treatment.